2015
DOI: 10.1111/trf.13066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of declining versus stable hemoglobin levels in whole blood donors

Abstract: The model can be used to predict to which group a donor belongs, and this prediction can be updated after each donation. This is of high practical importance because early identification of donors with declining Hb levels could help to tailor donation intervals and to prevent iron deficiency and donor deferrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Donors in Class III have a high initial Hb value and a moderately declining trajectory, donors in Class IV have moderate initial Hb value and relatively stable trajectory. The results of this study regarding the number of latent classes and the interpretation of each class are supported by a previous study [35]. …”
Section: Hemoglobin Longitudinal Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Donors in Class III have a high initial Hb value and a moderately declining trajectory, donors in Class IV have moderate initial Hb value and relatively stable trajectory. The results of this study regarding the number of latent classes and the interpretation of each class are supported by a previous study [35]. …”
Section: Hemoglobin Longitudinal Datasupporting
confidence: 88%
“…A Hb value of 8.4 mmol/l (135 g/l) and 7.8 mmol/l (125 g/l) for men and women, respectively, is widely accepted as the lower cut-off value of eligibility for donation to protect donors from anemia [34]. The previous studies showed that some individuals have a fast recovery, which results in a relatively stable trajectory, whereas others have a slow recovery that yields a declining trajectory in their Hb values [35, 36]. …”
Section: Hemoglobin Longitudinal Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study addressed a similar question by identifying factors associated with declining and stable Hb levels in blood donors. 21 Genome-wide association studies [22][23][24] have identified a number of loci regulating iron levels at a population level, but the value of these loci in predicting iron levels in a donor population is not known. It will be of interest to compare the frequencies of, for example, TMPRSS6 and HFE polymorphisms, which regulate iron levels, in frequent donors to those in the general population or infrequent donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, scientific knowledge on donor adverse reactions has significantly increased in the recent past years. This holds true particularly for causes and prevention of vaso-vagal reactions [24][25][26][27] and iron deficiency [28,29]. A future directive should include preventive measures acknowledged as effective to prevent donor reactions and to make donations safer for the donors.…”
Section: Donor Safetymentioning
confidence: 94%